Accident Law: An Excessive Standard May Be Efficient - Laszlo Goerke (Center for Economic Studies and ifo Institute (CESifo), 2001)
In a world with risk-neutral agents, liability rules will only induce efficient behaviour if these rules impose the full (marginal) costs of an action on the parties. However, institutional restrictions or bilateral activity choices can prevent the full internalisation of costs. A mechanism is proposed which guarantees an efficient outcome: monetary fines which are not related to the occurrence of an accident. Such a mechanism requires individuals to violate the standard of care in order to trigger fine payments. Hence, efficiency needs an excessive standard.
Keywords: 330; accident law; activity; care; efficiency; fines; standards of care; tort law